Efektivitas Media Video Tutorial Dalam Membuat Sup Ayam Bagi Siswa Tunarungu (Pre-Eksperiment Kelas X SMALB di SLB Luak Nan Bungsu) - Deswanti, Wika; Z, Martias (Universitas Negeri Padang, 2021)
This study was conducted by the author at SLB Luak Nan Bungsu. This research discusses how the learning activities taught by food are not much innovation. Judging from the mistake, the author tries to teach making different types of cooking skills and different ways of teaching chicken soup. This study uses experimental research method in the form of Pre experiment design with type one group pretest-posttest. And processed and compared to using Wilcoxon Rank Test. The result of this study is an increase in students' proficiency in making chicken soup after being treated in the form of treatment with video tutorials proven through the Wilcoxon Sign Rank Test, the average score obtained at the time of pretest 52.60 while the posttest score obtained the results of 90.20. Data processed using Wilcoxon Sign Rank Test obtained thitung value = 15. Seen in the test table, critical values at the level of error ( α ) 0.05 and n = 5 obtained Ttabel = 0 then Thitung = 15 > Ttabel = 0, therefore Ha received and Ho rejected. Thus it can be concluded that the video tutorial media is effective in making chicken soup.